The impact of family factors and digital technologies on mental health in university students - Gandarillas, Miguel Ángel; Elvira-Zorzo, María Natividad; Pica-Miranda, Gabriela Alicia; Correa-Concha, Bernardita (Frontiers in Psychology, 2024)
A substantial body of research indicates an increasing prevalence of mental health issues among university students in a range of countries. A number of psychosocial factors have been put forth in the research literature as possible explanations for this persistent decline in psychological wellbeing in higher education. The present study focused on the role of family factors and the use of digital technologies by students. A replication study was conducted at the University of the Americas (Chile) based on a previous study on psychosocial factors of academic learning patterns and mental health of university students at Complutense University of Madrid (UCM, Spain). A cross-sectional design was employed, using the same questionnaire, plus indicators of most frequently used digital technologies by the students. The questionnaire was administered online at the same time to all incoming students, gathering a sample of 4,523 students. A series of multiple regressions and ANOVAs were conducted to ascertain the extent to which family and digital factors could be identified as predictors of mental health indicators. The results indicate that key risk factors for mental health problems include high levels of parental protection and control/discipline, and especially the high use of social media and smartphones. In addition, the results suggest strategies to promote wellbeing, with a focus on the psychosocial diversity within an inclusive university community. Social and digital innovation, collective entrepreneurship, and participatory place-building may facilitate knowledge-value networks of artistic, cultural, ecological, and sports spaces to promote the sense of university community. A longitudinal follow-up on the same sample across academic years will reveal the extent to which these impacts are maintained through university study.